2017
DOI: 10.11591/ijece.v7i6.pp3622-3631
|View full text |Cite
|
Sign up to set email alerts
|

Efficient End-to-End Secure Key Management Protocol for Internet of Things

Abstract: Internet of things (IoT) has described a futurevision of internetwhere users, computing system, and everyday objects possessing sensing and actuating capabilities are part of distributed applications and required to support standard internet communication with more powerful device or internet hosts. This vision necessitates the security mechanisms for end-to-end communication. A key management protocol is critical to ensuring the secure exchange of data between interconnecting entities, but due to the nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Only the intended recipient can decipher the received packets. An efficient key-management protocol [19][20][21] is used to generate and manage the keys in the proposed system. There are many challenges exist in the cyber security management for IIoT [22].…”
Section: B Data-level Security In the Ncsamentioning
confidence: 99%
“…Only the intended recipient can decipher the received packets. An efficient key-management protocol [19][20][21] is used to generate and manage the keys in the proposed system. There are many challenges exist in the cyber security management for IIoT [22].…”
Section: B Data-level Security In the Ncsamentioning
confidence: 99%
“…The outcomes were suggested that this provides the better privacy without affecting the security level. Slimane and Ahmed [41] presented a secure key (end-to-end) management protocol for IoT and found effective with symmetric cryptography.…”
Section: Conventional Security Solution Approaches In Iotmentioning
confidence: 99%
“…The HLPSL is an expressive, modular, role-based, formal language that is used to specify control-flow patterns, data-structures, alternative intruder models and complex security properties, as well as different cryptographic primitives and their algebraic properties [21].…”
Section: Formal Verificationmentioning
confidence: 99%